The effect of irradiation on the flavor and aroma of coffee beans (Coffea robusta L) - Embuscado, Milda Evangelista; Acevedo, Teresita P.
Preliminary studies showed that irradiation at a dosage levels of 25 to 100 krad is effective in destroying the adults of coffee bean weevil, Araecerus fasciculatus. All the insects were killed in two to three weeks in time. Coffee beans (Robusta species) were subjected to the same level of irradiation. These were examined for moisture content, soluble solids, fat content, peroxide value, iodine value, acid value, total acidity and volatile acidity. The volatile acids were qualitatively and quantitatively determined using a Carlo Erba gas chromatograph. The samples were likewise subjected to sensory evaluation and the consumer-type evaluation for preference. The above tests were also conducted every month for a period of 4 months. Results were analyzed using the Hewlett Packard 85 computer to compute for the analysis of variance for the results of sensory evaluation and the coefficient of correlation for the results of the chemical tests. The computed r values showed that the moisture and fat contents were not affected by irradiation. The soluble solids has significant increase on the 4th month of storage only. The peroxide and iodine values of the coffee oil were observed to have a high degree of correlation with irradiation levels and storage. The peroxide value has a direct relationship with dosage and storage while iodine value has an inverse relationship with these two variables. Based on the linear regression equations of peroxide value and dose, the irradiated samples can be stored for a minimum of two years before they can attain a peroxide value of about 20 meq/100 g of fat, the level of rancidity which is generally perceptible to the panelists. The total volatile acidities have positive correlation with dose and storage time. Most of the acids produced due to the effect of irradiation were found to be volatile acids. Two acids, namely acetic and propionic acids were identified using gas chromatography. There is an increase in the concentration of the volatile acids on irradiation and upon storage. Results of the sensory evaluation showed that the selected panelists and consumer-panelists were not able to detect any changes or differences in control and irradiated coffee beans on he 0 day up to 4 months of storage.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Coffee -- Effect of radiation on; Radiation preservation of food